Robert Coleman-Senghor, 1940–2011 - Hester Williams, Kim D.; Moten, Fred (Kalfou (Santa Barbara, Calif.), 2017)
Robert Coleman-Senghor, Bob, was an intellectual giant. A maverick. An iconoclast. This was, in fact, not fully acknowledged—or respected—until after his death. Bob lived and breathed the life of the mind, every day. He loved education. He loved the university. He loved attaining and exchanging knowledge. He loved demonstrating his facility to cross fields and disciplines. There wasn’t a reference, an allusion, a classic or contemporary literary text, or a theory that you could ask him about with which he was not conversant. Yet during his lifetime, as so many faculty of color have experienced, the university, a place he loved to occupy, did not treat Bob kindly. Bob felt and experienced deeply his marginalization as a minoritized subject dogged by the university’s contradictions. Nonetheless, he was widely known for mastering these dictates of Western culture and society and using his mastery to confront and expose the university’s masked hegemony and circumscribed democracy. Bob insisted on making space for himself and other minoritized university subjects. He never backed down. He never wavered. He endured inside what Fred Moten describes as a space “always in the break, always the supplement of the general intellect and its source.”